The ketolide antibiotics HMR 3647 and HMR 3004 are active against Toxoplasma gondii in vitro and in murine models of infection. - Araujo, F G (1997)
Ketolides are a new class of macrolide antibiotics that have been shown to be active against a variety of bacteria including macrolide-resistant bacteria and mycobacteria. We examined two ketolides, HMR 3647 and HMR 3004, for their in vitro and in vivo activities against the protozoan parasite Toxoplasma gondii. In vitro, both ketolides at concentrations as low as 0.05 microg/ml markedly inhibited replication of tachyzoites of the RH strain within human foreskin fibroblasts. HMR 3004 demonstrated some toxicity for host cells after they were exposed to 5 microg of the drug per ml for 72 h. In contrast, HMR 3647 did not show any significant toxicity even at concentrations as high as 25 microg/ml. In vivo, both ketolides provided remarkable protection against death in mice lethally infected intraperitoneally with tachyzoites of the RH strain or orally with tissue cysts of the C56 strain of T. gondii. A dosage of 100 mg of HMR 3647 per kg of body weight per day administered for 10 days protected 50% of mice infected with tachyzoites. The same dosage of HMR 3004 protected 100% of the mice. In mice infected with cysts, a dosage of 30 mg of HMR 3647 per kg per day protected 100% of the mice, whereas a dosage of 40 mg of HMR 3004 per kg per day protected 75% of the mice. These results demonstrate that HMR 3647 and HMR 3004 possess excellent activities against two different strains of T. gondii and may be useful for the treatment of toxoplasmosis in humans.